2002
DOI: 10.1097/00003246-200201001-00004
|View full text |Cite
|
Sign up to set email alerts
|

Macrophage migration inhibitory factor

Abstract: Macrophage migration inhibitory factor (MIF) has been proposed to be the physiologic counter-regulator of glucocorticoid action within the immune system. In this role, MIF's position within the cytokine cascade is to act in concert with glucocorticoids to control both the "set point" and the magnitude of the inflammatory response. As well as overriding the immunosuppressive effects of glucocorticoids, it is now well established that MIF has a direct proinflammatory role in inflammatory diseases, such as sepsis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
180
0
17

Year Published

2004
2004
2016
2016

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 227 publications
(201 citation statements)
references
References 83 publications
4
180
0
17
Order By: Relevance
“…MIF reportedly promotes inflammatory cytokine release through the CD74 receptor, and it is closely related to the inflammatory cytokines expressed in degenerated intervertebral disc tissues [6,23,24,32]. However, the inflammatory role of MIF and CD74 in cartilage end plate largely remains unclear.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…MIF reportedly promotes inflammatory cytokine release through the CD74 receptor, and it is closely related to the inflammatory cytokines expressed in degenerated intervertebral disc tissues [6,23,24,32]. However, the inflammatory role of MIF and CD74 in cartilage end plate largely remains unclear.…”
Section: Discussionmentioning
confidence: 99%
“…Macrophage migration inhibitory factor (MIF) is a multifunctional cytokine that plays an important role in many pathophysiologic responses in vivo [6,23,24]. As an important proinflammatory cytokine, MIF can counteract glucocorticoid signaling by activating immune or inflammatory cells and promoting inflammatory cytokine release [9].…”
Section: Introductionmentioning
confidence: 99%
“…In other studies, however, the induction of AHR was observed despite the absence of infiltrating eosinophils, suggesting dissociation between these phenomena [6][7][8][9][10]. Macrophage migration inhibitory factor (MIF) is a pleiotropic molecule and critical mediator of innate and acquired immune responses [11,12]. Pre-formed MIF protein is present in many cell types and is released in response to different stimuli, such as infection and cytokine stimulation [12].…”
Section: Introductionmentioning
confidence: 99%
“…Macrophage migration inhibitory factor (MIF) is a pleiotropic molecule and critical mediator of innate and acquired immune responses [11,12]. Pre-formed MIF protein is present in many cell types and is released in response to different stimuli, such as infection and cytokine stimulation [12].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation